2011
DOI: 10.1007/s10895-011-0941-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on Aequorea Green Fluorescent Protein Anionic and Neutral Chromophore Forms Fluorescence

Abstract: The emission behaviour of Aequorea green fluorescent protein (A-GFP) chromophore, in both neutral (N) and anionic (A) form, was studied in the temperature range from 20°C to 75°C and at pH=7. Excitation wavelengths of 399 nm and 476 nm were applied to probe the N and A forms environment, respectively. Both forms exhibit distinct fluorescence patterns at high temperature values. The emission quenching rate, following a temperature increase, is higher for the chromophore N form as a result of the hydrogen bond n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Temperature dependence of the fluorescence intensity of the emGFP-Mito is inverse compared to wt-GFP. In the case of emGFP-Mito increased temperature induces reduction of the hydrogen-bond network resulting in a decrease of fluorescence intensity as has been observed elsewhere 48 . The fluorescence intensity images of HeLa cells expressed with emGFP-Mito at 23–39 °C temperature is shown in Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Temperature dependence of the fluorescence intensity of the emGFP-Mito is inverse compared to wt-GFP. In the case of emGFP-Mito increased temperature induces reduction of the hydrogen-bond network resulting in a decrease of fluorescence intensity as has been observed elsewhere 48 . The fluorescence intensity images of HeLa cells expressed with emGFP-Mito at 23–39 °C temperature is shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…1a. This spectroscopic feature was reported in the Aequorea GFP and attributed to a dipolar moment variation, resulting from a charge density transfer occurring between the close neighbors oxygen atoms 48 . Dipolar change reorganizes molecules around the electronic excited state decreasing its energy leading to observed red shift of emission maximum 49 .…”
Section: Resultsmentioning
confidence: 56%
“…As demonstrated above, a low temperature during the clearing procedure facilitated the preservation of EGFP fluorescence. Previous studies have indicated that the fluorescence intensity of EGFP is also thermally sensitive ( 46 , 47 ). A higher temperature can increase the probability of GFP unfolding; moreover, the thermally induced enhancement of collisions between molecules would probably increase fluorescence quenching.…”
Section: Discussionmentioning
confidence: 99%
“…The quenching of GFP is also significantly affected by temperature (dos Santos 2012, Schwarz et al 2015. Incubation at elevated temperature may denature GFP proteins while promoting tissue clearing.…”
Section: Preservation Of Fluorescent Signals From Reporter Proteinsmentioning
confidence: 99%